A Ka-Band Horn Antenna Excited With Parasitic Dielectric Resonator Antenna - Othman, A; M F, Ain; Sulaiman, A A; Othman, M A (2010)
A pyramidal horn antenna excited with parasitic dielectric resonator (DR) antenna for use at Ka-band frequencies is proposed.